Guns germs & steel: A short history of everybody for the last 13000 years - Diamond, Jared (London Vintage, 2017)
This book details that till about 11,000 B.C. the people living in the world were primarily of the Stone Age group. It was roughly at that point of time that a breaking off happened, which slowly led to the evolution of societies and groups. Gradually, people started getting involved in farming and rearing numerous plants and animals in parts of Eurasia and parts of the Americas. There was a gradual rise of planters and animal domesticators.